2005
DOI: 10.3758/bf03206497
|View full text |Cite
|
Sign up to set email alerts
|

A spatial explanation for synchrony biases in perceptual grouping: Consequences for the temporal-binding hypothesis

Abstract: If two images are shown in rapid sequential order, they are perceived as a single, fused image. Despite this, recent studies have revealed that fundamental perceptual processes are influenced by extremely brief temporal offsets in stimulus presentation. Some researchers have suggested that this is due to the action of a cortical temporal-binding mechanism, which would serve to keep multiple mental representations of one object distinct from those of other objects. There is now gathering evidence that these stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…However, we found that orientation discrimination and letter recognition were possible with phantom "E"s under ramped onset and offset, but that the threshold was dependent on the rate of change of contrast in a fixed relationship-the contrast velocity. The fact that the stimuli were turned on and off over a varying number of frames, with threshold forming a fixed relation with duration, makes it unlikely that stimulus perception for phantom contours is strongly related to fixational eye movements (Wallis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that orientation discrimination and letter recognition were possible with phantom "E"s under ramped onset and offset, but that the threshold was dependent on the rate of change of contrast in a fixed relationship-the contrast velocity. The fact that the stimuli were turned on and off over a varying number of frames, with threshold forming a fixed relation with duration, makes it unlikely that stimulus perception for phantom contours is strongly related to fixational eye movements (Wallis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On a given trial, however, alternate row (or column) elements were presented on two successive display frames. Despite having the appearance of a single grid flashed in its entirety, observers were able to reliably group the grid into rows or columns in accordance with the temporally asynchronous stimuli presentations (Usher & Donnelly, 1998; Dakin & Bex, 2002; Wallis, 2005; Wallis, 2006). Wallis (2006) proposed a purely spatial explanation for these results, suggesting that small, fixational eye movements—specifically, the small-amplitude and high-frequency tremor eye movements—occurring between the asynchronous presentation of grid elements results in a spatial shift of grid elements on the retina.…”
Section: Introductionmentioning
confidence: 99%
“…Fixational eye movements follow a self-avoiding random walk (Engbert, Mergenthaler, Sinn, & Pikovsky, 2011; Herrmann, Metzler, & Engbert, 2017), making it difficult to systematically investigate the precise relationship between retinal slip and perceptual grouping. Wallis has argued that the grouping effect is likely due to tremor eye movements because of their speed (Wallis, 2005; Wallis, 2006). Despite drift eye movements resulting in large amplitude eye movements, their speeds are relatively low and are unlikely to result in sufficiently large stimulus shifts from one frame to the next (Wallis, 2005; Wallis, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shadlen and Movshon, 1999;Wallis, 2005;see Treisman, 1999). Visual stimuli contain many distinguishable features, and the visual system has a corresponding proliferation of feature representations at multiple cortical stages (Felleman and van Essen, 1991).…”
mentioning
confidence: 99%